Gamma‐glutamyl‐transferase may predict COVID‐19 outcomes in hospitalised patients. Issue 12 (8th October 2021) - Kasapoglu, Benan; Yozgat, Ahmet; Tanoglu, Alpaslan; Can, Guray; Sakin, Yusuf Serdar; Kekilli, Murat
Abstract: Aim: In this study, we aimed to define the predictive role of liver function tests at admission to the hospital in outcomes of hospitalised patients with COVID‐19. Material and Method: In this multicentric retrospective study, a total of 269 adult patients (≥18 years of age) with confirmed COVID‐19 who were hospitalised for the treatment were enrolled. Demographic features, complete medical history and laboratory findings of the study participants at admission were obtained from the medical records. Patients were grouped regarding their intensive care unit (ICU) requirements during their hospitalisation periods. Results: Among all 269 participants, 106 were hospitalised in the ICU and 66 died. The patients hospitalised in ICU were older than patients hospitalised in wards ( P  = .001) and expired patients were older than alive patients ( P  = .001). Age, elevated serum D‐dimer, creatinine and gamma‐glutamyl transferase (GGT) levels at admission were independent factors predicting ICU hospitalisation and mortality in COVID‐19 patients. Conclusion: In conclusion, in hospitalised patients with COVID‐19, laboratory data on admission, including serum, creatinine, GGT and d‐dimer levels have an important predictive role for the ICU requirement and mortality. Since these tests are readily available in all hospitals and inexpensive, some predictive formulas may be calculated with these parameters at admission, to define the patients requiring intensive care.